2021
DOI: 10.1111/psyp.13941
|View full text |Cite
|
Sign up to set email alerts
|

The extrastriate symmetry response is robust to variation in visual memory load

Abstract: An Event Related Potential response to visual symmetry, known as the Sustained Posterior Negativity (SPN), is generated whether symmetry is task relevant or not, and whether symmetry is attended or not. However, no study has yet examined interference from concurrent memory tasks. To answer this fundamental question, we investigated whether the SPN is robust to variation in Visual Working Memory (VWM) load. In Experiment 1 (N = 24), each trial involved a sample display, a probe and a test display. Sample and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The SPN is very robust to experimental manipulations of task, but not completely indifferent to them [149,[157][158][159]. Makin et al [141] found that the parametric SPN response was comparable across five tasks but selectively enhanced when participants attended to regularity (Figure 4).…”
Section: Top-down Effects On Spn Amplitudementioning
confidence: 98%
“…The SPN is very robust to experimental manipulations of task, but not completely indifferent to them [149,[157][158][159]. Makin et al [141] found that the parametric SPN response was comparable across five tasks but selectively enhanced when participants attended to regularity (Figure 4).…”
Section: Top-down Effects On Spn Amplitudementioning
confidence: 98%
“…Figure from Makin et al (2022). Derpsch et al (2019) found that whilst the brain response to symmetry can be enhanced when symmetry is presented in attended regions of the screen, it is still robust when symmetry is presented unattended regions. In addition, Derpsch et al (2021) found that the SPN is not diminished by a concurrent visual working memory task, suggesting the SPN is also robust to variations in visual memory load.…”
Section: Hosted Filementioning
confidence: 99%
“…Almost half the SPNs (125/249) were recorded in experiments where participants were engaged in active regularity discrimination (e.g., press one key to report symmetry and another to report random). The other 124 SPNs were recorded in conditions where participants were performing a different task, such as discriminating the colour of the dots or holding information in visual working memory ( Derpsch et al, 2021 ). In most projects the stimuli were presented for at least 1 second and the judgment was entered in a non-speeded fashion after stimulus offset.…”
Section: Introductionmentioning
confidence: 99%